2012
DOI: 10.1002/ptr.4745
|View full text |Cite
|
Sign up to set email alerts
|

Mild Mitochondrial Depolarization is Involved in a Neuroprotective Mechanism of Citrus sunki Peel Extract

Abstract: Mitochondrial membrane potential (∆Ψm ) contributes to determining a driving force for calcium to enter the mitochondria. It has been demonstrated that even a small mitochondrial depolarization is sufficient to prevent mitochondrial calcium overload and the subsequent apoptosis. Therefore, mild mitochondrial depolarization has been recently evaluated as a novel mechanism of neuroprotection via inhibiting neurotoxic mitochondrial calcium overload during neuronal insults. In the present study, using both real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This might account for the superior mitochondrial ROS mitigating property of PBE over catechin. Such mild depolarization has been attributed to the neuroprotective effect of a plant extract [42] and the protection of cardiomyocytes from oxidative stress [40]. In the case of PBE, further studies are warranted to identify the active molecules and the underlying mechanisms involved in its mild mitochondrial potential depolarization propensity.…”
Section: Discussionmentioning
confidence: 99%
“…This might account for the superior mitochondrial ROS mitigating property of PBE over catechin. Such mild depolarization has been attributed to the neuroprotective effect of a plant extract [42] and the protection of cardiomyocytes from oxidative stress [40]. In the case of PBE, further studies are warranted to identify the active molecules and the underlying mechanisms involved in its mild mitochondrial potential depolarization propensity.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of a plant extract was once attributed to the mild depolarization of ΔΨ m [59]. The mitochondrial membrane potential (ΔΨ m ) contributes significantly to the extent of ROS production and with increased production occurring at high potentials [60].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that soybean isoflavones inhibit growth of prostate cancer cell in vivo (Choi et al ., ) and in vitro (Bosland et al ., ; Hikosaka et al ., ). The intake of citrus fruits was considered beneficial for health (Onda et al ., 2013; Wu et al ., ), and in a recent literature review of citrus flavonoids, a broad spectrum of biological activities, including anticarcinogenic and antitumor activities, was discussed (Gullett et al ., ; Lu et al ., 2012). It is commonly accepted that cancer development can be prevented by the ingestion of certain foods (Stavric, ), and flavonoids in citrus fruits and juices are examples of the most prominent cancer‐preventing agents.…”
Section: Discussionmentioning
confidence: 99%